Systemic inflammatory response indicators in patients with neck phlegmons - Shaprynskyy, V. O.; Kryvetskyy, V. F.; Suleymanova, V. H.; Mityuk, B. O.; Khmelevska, T. A. (Modern medical technology, 2019)
Purpose of the study. To study systemic inflammatory response indexes in patients with neck phlegmons. Materials and methods. All patients were divided on two groups. In general group (84 people) treatment included vulnerosorption with modern composition. The control group consisted of 57 patients taking hydrophilic ointments. To investigate the severity of endotoxicosis, Morozova’s scales and predictors of leukocyte index of intoxication, the index of the ratio of neutrophils and lymphocytes, lymphocyticgranulocyte index, were used. Results. The most frequent complications included sepsis (64,5%), toxic myocarditis (60%), toxic nephritis (68%) and mediastinitis (48,2%). Morozov’s index of 113 (80%) patients was 41,5 ± 5 (severe endogenous intoxication); among the last 28 (20%) it showed 29,7 ± 2,6 (the average degree of intoxication). Changes of leukocyte index of intoxication, the index of the ratio of neutrophils and lymphocytes, lymphocytic-granulocyte index in patients treated with sorption composition showed more positive dynamics compared with the control group. The mortality in general group was 4,8% vs 14% in the control group. Conclusions. Deep neck phlegmons are characterized by severe endotoxicosis and lead to sepsis in 64,5% and mediastinitis in 48,2% cases. Morozova’s scales are useful to study the level of endotoxicosis in patients with neck phlegmons. Investigated sorption composition is more effective than a hydrophilic ointment, what confirms the dynamics of leukocyte index of intoxication, the index of the ratio of neutrophils and lymphocytes, lymphocytic-granulocyte index.